Crystal structure and Hirshfeld surface analysis of (2,7-diethoxynaphthalene-1,8-diyl)bis[(4-bromophenyl)methanone] - Kun Li; Jiali Yao; Hiroaki Iitsuka; Noriyuki Yonezawa; Akiko Okamoto (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, C28H22Br2O4, crystallizes in the monoclinic space group P21/c at 193 K. The two 4-bromobenzoyl groups are attached in a non-coplanar fashion to the naphthalene ring system and are oriented in opposite directions. The two 4-bromobenzene rings are tilted almost symmetrically with respect to the naphthalene ring system. The crystal packing features several kinds of non-classical hydrogen bonds such as C—H...X (X = polar atom), in which the C—H group acts as a hydrogen-atom donor, and C—H...π interactions. The two-dimensional fingerprint plots generated in a Hirshfeld surface analysis show non-classical hydrogen bonding with short contacts involving the bromo group.